A normalized-relative-displacement-vibration-shape (NRDVS)-based structural damage assessment scheme. Issue 3 (3rd July 2018) - Chu, Shih-Yu; Wu, Ruei-Lin
ABSTRACT: Observing the change of modal frequency to detect damage is popular in structural health monitoring systems because damage is always related to a reduction of stiffness as well as modal frequency. However, large deformation or inelastic behavior of structure may occur after a catastrophic earthquake event. The inter-story drift ratio is a straightforward indicator to perform the damage assessment. The normalized-relative-displacement-vibration-shape (NRDVS) proposed herein is an averaging profile from time-varying vectors that can be integrated from measured acceleration records. The corresponding normalized inter-story drift ratio (NIDR) can be calculated by differencing the normalized displacements of the two successive floors of NRDVS and dividing by the story height. The relationships between degradation on column stiffness, NRDVS and NIDR of SAP2000 models and shaking table steel frame models are studied to assess the local damage behavior. Both NRDVS and NIDR are insensitive to the intensity of earthquake input provided that the system remains within its elastic range. The proposed NIDR will be increased with respect to its original (healthy) case on the floor where the column degradation occurred. The sensitivity of increment on NIDR due to stiffness degradation is higher than the reduction of the fundamental frequency. The proposed NRDVS-based damage assessment scheme is to provide a rapid damage assessment tool for aftershock rapid screening of buildings. Therefore, the damaged floor instead of exact damage location can be revealed rapidly to give quantitative information for field professional engineers to perform detailed on-site investigation. The local damage behavior can be identified based on observing the variations of NIDRs and a rapid damage assessment scheme can be embedded in the processors of accelerometer systems for rapid aftershock evaluation.